DC-DC Converter for Fuel Cell Application - N.F.A. Hamid (2013)
Nowadays, the interest for green energy source for domestic used has increased rapidly. The source can be either renewable energy like solar and wind or alternative energy like fuel cell. Currently, the fuel cell has been used as energy source in many applications such as in hybrid car, vending machines, vacuum cleaner and high road sign. Fuel cell output voltage is varied wisely and low in magnitude (<60V for a system <10kW). Therefore, the step up DC-DC converter is essential to generate high regulated DC voltage. The main purpose of this project is to develop a high efficiency DC-DC converter for fuel cell application. This converter will boost up the DC input voltage to more useful high DC voltage. This high voltage can be used to power up DC devices or can be used as an input for DC-AC converter. This converter produce low ripple for output current and voltage which cause low harmonics and noise produce by the device.